2005
DOI: 10.1007/s11240-005-1313-8
|View full text |Cite
|
Sign up to set email alerts
|

Storability and germination of sodium alginate encapsulated somatic embryos derived from the vegetative shoot apices of mature Pinus patula trees

Abstract: Storability and germination of sodium alginate encapsulated somatic embryos derived from vegetative shoot apices of mature Pinus patula trees were tested on half strength DCR basal medium without growth regulators. The germination percentage of encapsulated somatic embryos was affected significantly by the concentration of sodium alginate and the duration of exposure to calcium chloride. Somatic embryos encapsulated with 2.5% sodium alginate dissolved in DCR basal salts gave significantly higher germination (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 24 publications
5
22
0
Order By: Relevance
“…Encapsulated somatic embryos of Pinus patula stored at 2 or 4°C for four months showed high conversion rates (73 to 61%, resp. ), but when stored at higher temperatures (e.g., room temperature 27°C) for 40 days they showed only 6% conversion (Malabadi and van Staden 2005). The conversion percentage decreased with an increase in storage time and temperature.…”
Section: Discussionmentioning
confidence: 97%
“…Encapsulated somatic embryos of Pinus patula stored at 2 or 4°C for four months showed high conversion rates (73 to 61%, resp. ), but when stored at higher temperatures (e.g., room temperature 27°C) for 40 days they showed only 6% conversion (Malabadi and van Staden 2005). The conversion percentage decreased with an increase in storage time and temperature.…”
Section: Discussionmentioning
confidence: 97%
“…Several researchers suggest that to control growth and facilitate the germination of somatic embryogenesis, the synthetic endosperm can simulate an endosperm of sexual origin, containing one or several compounds such as: nutrients, growth regulators, anti-pathogens, herbicides, biocontrollers and bio-fertilizers, among others, with the aim of ensuring the conversion of the plant and its development in the field (Castillo et al 1998, Kumar et al 2004, Malabadi and Staden 2005.…”
Section: Introductionmentioning
confidence: 99%
“…A 100% conversion rate of Rotula aquatic artificial seeds produced by the encapsulation of its somatic embryos was achieved when the artificial seeds were cultured in MS medium [54]. Malabadi and Staden [60] and Manjkhola et al [61] reported conversion rates of 89% and 60.6% of encapsulated somatic embryos of Pinus patula and Arnebia euchroma, respectively. The encapsulated somatic embryos of Acca sellowiana had a high conversion rate that was about 80% after 1.5-years storage [62].…”
Section: Somatic Embryosmentioning
confidence: 99%
“…The endosperm of artificial seeds could be similar to the endosperm of seeds, but can also be manipulated so as to control growth and reduce the difficulties of the germination of somatic embryos [53,60,81]. While Saiprasad [8] mentioned that usually 3% sodium with complexing solution containing 75 mM Ca 2 Cl 2 ·2H 2 O for half an hour mixing duration provides the optimal structure for artificial seed bead formation, Ara et al [6] indicated that generally 2% sodium alginate gel upon complexation with 100 mM CaCl2·2H2O is the best.…”
Section: Artificial Endosperm Structure and Their Effects In The Artimentioning
confidence: 99%
See 1 more Smart Citation